Pneumatic conveying of solids a theoretical and practical approach - Klinzing, George E. (Powder technology series., 1997)
The pneumatic conveying of solids is a fast growing technique for the handling of bulk powdered and granular materials in the mining, chemical and agricultural industries. Pneumatic Conveying of Solids covers both theoretical and practical aspects of the subject. It is unique in its blending of academic materials and good industrial design techniques. Each topic is covered in depth, with emphasis placed on the latest techniques, hardware systems and design and research methodology. Its comprehensive worked examples and tables ensure that the reader need not consult any other reference material. This second edition is thoroughly updated and has information on new techniques, procedures and experimental discoveries. Recent developments in the subject covered in this new edition include artificial intelligence, expert systems and neural network analysis.